Incidental detection of Tietze syndrome with costochondritis: A case report - Lister, Gilbert; Soekardi, Adi; Icksan, Aziza Ghanie (Jurnal Prima Medika Sains, 2025)
Background: Tietze syndrome represents a rare and atypical source of anterior chest discomfort, distinguished by localized tenderness and non-suppurative swelling, typically centered around the 2nd or 3rd costal cartilages. Despite diligent investigation, the precise underlying causes of Tietze syndrome remain elusive. Case Report: We present a case of a 35 year old male patient with suspected Tietze syndrome with costochondritis. He came in with complaints of abdominal pain and frequent coughs. He has a history of ADPKD and thalassemia since age 12. Tietze syndrome was an incidental finding in this patient. A thorax scan showed multiple nodular and lobulated lesions in the medial mediastinum; additionally, an abnormal widening and flattening of the costochondral junction of the ribs bilaterally. The CT scan findings reveal notable deformities characterized by widened and irregularly shaped anterior rib masses spanning the 1st to the 4th ribs bilaterally. The USG scan of the thorax showed a hypogenic thickening of the costochondral junction with vascularization. Discussion: Tietze's syndrome presents a diagnostic challenge necessitating comprehensive imaging modalities for accurate diagnosis. Ultrasound imaging stands out as the primary approach, showcasing conspicuous soft tissue swelling indicative of the ongoing inflammatory process. While computed tomography often reveals subtle focal swellings or mild sclerosis in the affected joint. Conclusion: The clinical manifestations frequently encompass an abrupt onset of chest discomfort devoid of antecedent trauma, predominantly observed among younger cohorts with an otherwise clean bill of health. Ultrasound is an accurate and effective modality to diagnose Tietze syndrome. This disease is frequently associated with other comorbidities such as rheumetic and autoimmune disorders.